DIGITAL TECHNOLOGIES IN THE MUSIC INDUSTRY OF KAZAKHSTAN - Babamuratov Darkhan (Foundations and Trends in Research, 2025)
This work is dedicated to studying the impact of digital technologies on the music industry in Kazakhstan. The research includes an analysis of theoretical literature focusing on the transformation of business models, methods of content creation and distribution, and copyright protection issues in the digital environment. Key trends and challenges facing the music industry in the context of digitalization are examined. It is shown that digital transformation requires a comprehensive approach that considers technological, legal, and cultural aspects. The conclusion emphasizes the need for the Kazakhstani music industry to adapt to the new realities of the digital economy and identifies directions for further research aimed at developing practical recommendations for market participants